Should Intra-Articular Steroidal Injection be Administered in TMJ Disorders - Kaustubh Sansare; V Sreenivasan (Wolters Kluwer Medknow Publications, 2004)
Any treatment modality has its pro & cons, the good or the bad, the need to the need not to. Same is with TMD where the patient comes to the clinic with intense pain. We as clinicians, will agree that the malady of pain in TMJ is on the rise. How do we deal with it, should we be conservative in our approach or should we go ahead with treatment modality, which have yet not been well documented. To do or not to do, Two clinicians from the field of oral medicine put forth their views.